Conservative treatment using a sponge cast for transfer fractures in nursing home patients - Cho HM (Dove Medical Press, 2019)
Hong Man Cho,1 Joon Soo Ha,2 Jae Woong Seo,1 Hyun Ju Lee,1 Sun Do Kim,1 Hyochoon Lee,1 Hyung Bae Park31Department of Orthopaedic Surgery, Gwangju Veterans Hospital, Gwangju, Korea; 2Department of Orthopaedics, King’s College Hospital, London, UK; 3Department of Biology, College of Chonbuk National University, Jeonju, KoreaBackground: Transfer fractures in the lower limbs of bedridden and chair-bound nursing home patients can result from trauma induced by the usual lifting, moving, turning, or transferring maneuvers. Treatment entails immobilization for pain control and position change; however, splints/hard casts increase the risk of pressure sores. Therefore, we evaluated the use of a sponge cast.Materials and methods: Between March 2011 and October 2017, 17 patients with a lower limb transfer fracture due to transferring maneuvers in a nursing home were recruited. We evaluated the improvement in pseudo-motion and divided the patients as having bony union, fibrous union, or remaining pseudo-motion. We also investigated the occurrence of pressure sores due to immobilization up until the final follow-up.Results: Femur fractures occurred in 15 patients and lower leg fractures in two. Six of the 15 femur fractures were periprosthetic (four hip arthroplasty and two knee arthroplasty). Pseudo-motion was improved in 15 of 17 cases, within an average of 17.3 weeks for the improvement (14–23 weeks; bony union: 11 cases and fibrous union: four cases). Pseudo-motion remained in two cases: one periprosthetic fracture around the knee arthroplasty and the other, a femur neck fracture. No pressure sores occurred.Conclusions: A sponge cast appears to be one of the effective treatment options available for bedridden or chair-bound patients with a lower limb fracture due to its low risk of complications and satisfactory clinical results.Keywords: transfer fracture, long bone fracture, conservative treatment, bedridden, immobile patients